Perception of Top Executives Towards the Relationship between Mission Statement Communication Variables and Firm Performance in Selected Public Listed Companies - Chook, Ka Joo (2005)
This study was undertaken to examine the perceptions of top executives of the relationships between the mission statement communication variables and firm performance in Malaysian. Despite the immense popularity of the concept of mission statement in the communication and management literature, limited empirical studies had been carried out to investigate the relationships between the mission statement communication variables and firm performance. The research design of the study was a survey research based on a structured questionnaire and also content analysis of the mission statement content. The informants were the Managing Directors and Chief Executive Officers of public listed firms in the Bursa Malaysia as of 23rd October 2003. One hundred and thirty six informants participated in the survey by returning the selfadministered questionnaire distributed to them in two batches of mail distribution. Beside the structural questionnaire, content analysis was conducted to measure the level of adequacy of mission statement content. The mission statements were compiled from the firm annual reports, websites and also personal requests. The dependent variable of the study, firm performance, was measured with four perceptual items; namely the satisfaction of the respondents with the performance of the firm based on sales, profit, growth and profit margin. To evaluate the convergent validity of the perceptual measurements, correlations were made between the perceptual values and two accounting ratios; Return on Sales and Return on Assets. The correlation coefficients showed positive and significant measurements between the perceptual values and the accounting ratios. The independent variables of the study consist of selected mission statement communication variables, identified from the literature on mission statement. Six mission statement communication variables (intensity of personal mode of mission statement communication, intensity of impersonal mode of mission statement communication, commitment of leaders in selling the mission statement, satisfaction with the communication efforts, credibility of the sellers and adequacy of mission statement content) were hypothesized to have significant effects on firm performance. The level of firm performance in the present study showed moderate level. Similarly, the analysis of the five mission statement communication variables also showed moderate level of satisfaction. The level of adequacy of mission statements content was analsyed using Ashridge Mission Model of mission statement. The content analysis showed that fifty seven percent of the mission statements analysed was inadequate in terms of their contents, as the mission statements do not contain the four contents needed in an effective mission statement. The results of the bivariate correlation analysis showed positive and significant relationships between four of the mission statement communication variables and firm performance except for the credibility of the mission sellers and adequacy of the mission statement contents. The multiple regression analysis revealed that only the intensity of personal mode of mission statement communication was observed to be good predictor of firm performance and this variable contributed 22 percent of the variation of firm performance in the study. The results suggest that the intensity of personal mode of mission statement communication play an important role and had direct relationship with the performance of firms. At the practical level, the present study has clarified the nature of the relationships between mission statement communication and firm performance. Only the intensity of personal mode of mission statement communication has a direct influence on firm performance. The results suggest that Managing Directors and Chief Executive Officers who want to achieve the goals of mission statement must be personally involved in the mission statement communication to the employees as their involvement will have the biggest impact on firm performance. Managers must also ‘walk the talk’ and ‘talk the walk’ the ideas of the mission statement to encourage the acceptance and adoption of the mission statement by using the mission statement as a strategic yardstick of how they manage the firms.